Official (ISC)2 guide to the CAP CBK - Howard, Patrick D. ((ISC)2 Press series., 2012)
"There are many elements that make system authorization complex. This book focuses on the processes that must be employed by an organization to establish a system authorization program based on current federal government criteria. Although the roots of this book address various federal requirements, the process developed and presented can be used by nongovernment organizations to address compliance and the myriad laws, regulations, and standards currently driving information technology security. The key to reaching system authorization nirvana is understanding what is required and then implementing a methodology that will achieve those requirements. The top-down methodology presented in this book provides the reader with a practical approach for completion of such an undertaking. By demystifying government requirements, this book presents a simplified, practical approach to system authorization"--